Implikasi Hukum Pemalsuan Akta Notaris terhadap Kekuatan Pembuktian - Ananda maprilia Janur putri; Novi Hendriani Putri; Triza Susana; Warni Laras Wahyuni (Jurnal Hukum Lex Generalis, 2026)
Notarial deeds as authentic documents possess perfect evidentiary value in civil law. Issues arise when forgery occurs, affecting their validity and evidentiary strength. This study aims to analyze the legal implications of notarial deed forgery and the resulting legal liabilities. The results show that forged deeds lose their authenticity and no longer hold perfect evidentiary value. Forgery also results in criminal, civil, and administrative liabilities. Therefore, stronger supervision and professional integrity of notaries are required.